Occult Hepatitis B Virus Infection Among Blood Donors in the Capital City of Addis Ababa, Ethiopia: Implications for Blood Transfusion Safety - Gemechu, Gizachew; Abagez, Woldearegay Erku; Alemayehu, Dawit Hailu; Tesfaye, Abebech; Tadesse, Demewoz; Kinfu, Abiy; Mihret, Adane; Mulu, Andargachew (Frontiers in Gastroenterology, 2022)
Background Occult hepatitis B virus infection (OBI) remains a potential threat to blood safety in developing countries. Nevertheless, there is no data available on the magnitude of occult hepatitis among blood donors in Ethiopia. Therefore, this study aimed to estimate the magnitude of OBI among blood donors in Ethiopia. Objectives The aim of this study is to determine the magnitude of OBI and associated risk factors among blood donors at the National Blood Bank, Addis Ababa, Ethiopia. Methods A total of 973 HBsAg-negative plasma samples were tested for anti-HBc antibody using an ELISA and viral DNA using automated ABBOTT real-time PCR. Along with plasma samples, demographic data were retrieved from the database with respect to donors. Both descriptive and inferential statistics were employed for the analysis of data by SPSS 20. p-values less than 0.05 were considered as statistically significant. Results Of the total of 973 study participants, 445 (45.7%) were female with a mean age of 26.5 years. A total of 144 (14.8%) blood samples were anti-HBc antibody reactive. Four (0.41% of all samples, and 2.8% of anti-HBc-positive samples) samples were confirmed to have OBI by DNA detection. The mean viral load among the confirmed OBI samples was 31 IU/ml with ±12 SD, suggesting true occult hepatitis BV infections. Age was found to be a risk factor for anti-core positivity and was statically significant at p = 0.0001. Conclusion About four out of 1,000 blood donors screened negative with HBsAg had occult HBV infection. This shows that there could be a risk of HBV transmission through blood transfusion in Ethiopia. Therefore, there is a need for further investigation and action to revise the existing blood screening strategy by including anti-HBc and HBV nucleic acid testing.